ICLA: Seventy Years of Literary Research Bringing the Cultures of the World Closer (El Hilo de la Fabula, 2025)
The International Comparative Literature Association (ICLA) Congress held in Korea was an ideal occasion to commemorate seventy years of research work, carried out with unquestionable scientific rigor and a deep commitment to dialogue and appreciation of diversity. Fully aligned with these principles, the association has been modernized through the incorporation of technology, which was used not only as a tool for communication and work but also as a subject of study, to analyze its use in relation to culture. Looking towards the future, the association has also generously welcomed young researchers. These innovations were reflected in the development of the congress, which brought together over 1,400 researchers from 40 countries.
Keywords: comparative literature; technology; cultural heritage; human connections